2017
DOI: 10.1038/srep45697
|View full text |Cite|
|
Sign up to set email alerts
|

Cassava foliage affects the microbial diversity of Chinese indigenous geese caecum using 16S rRNA sequencing

Abstract: Geese are extremely adept in utilizing plant-derived roughage within their diet. However, the intestinal microbiome of geese remains limited, especially the dietary effect on microbial diversity. Cassava foliage was widely used in animal feed, but little information is available for geese. In this study, the geese were fed with control diet (CK), experimental diet supplemented with 5% cassava foliage (CF5) or 10% (CF10) for 42 days, respectively. The cecal samples were collected after animals were killed. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 40 publications
7
46
0
Order By: Relevance
“…Most of gramineae grasses were low in nutritional value as they have high moisture and fiber content but low protein content. In contrary, legume and foliage normally have low moisture and high protein content (Li, Zhou, Pan et al, ; Li, Zhou, Zi et al, ; Syahniar, Ridla, Jayanegara, & Samsudin, ). Their mixtures as silage have good fermentation quality and balanced nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of gramineae grasses were low in nutritional value as they have high moisture and fiber content but low protein content. In contrary, legume and foliage normally have low moisture and high protein content (Li, Zhou, Pan et al, ; Li, Zhou, Zi et al, ; Syahniar, Ridla, Jayanegara, & Samsudin, ). Their mixtures as silage have good fermentation quality and balanced nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Its foliage contains high protein content, gross energy and mineral elements and can be used as animal feed (Napasirth, Napasirth, Sulinthone, Phommachanh, & Cai, ). Many studies have explored the effects of cassava foliage (CF) on diet of goats, sheep, pig and poultry and found that it could positively affect the growth performance, carcass characteristics, digestion and digestive organ development (Borin, Lindberg, & Ogle, ; Fasae, Adu, Aina, & Dipeolu, ; Li, Zhou, Pan et al, ; Nguyen, Ngoan, Bosch, Verstegen, & Hendriks, ; Oni, Arigbede, Oni, & Onwuka, ; Régnier, Bocage, & Archimède, ). The CF is generally used for animals in fresh or silage, and the fermentation quality of cassava silages without additive is acceptable (Man & Wiktorsson, ; Napasirth et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2011) analysed the microbial diversity of geese caecum at the class level using 16S rRNA clone library approach, and the caecal microbiome of geese are dominantly occupied by 58.7% Clostridia (Firmicutes), 26.9% Bacteroidetes (Bacteroidetes) and 11.2% Erysipelotrichi (Firmicutes), showing similar results with the caecal microbiome of chickens. Li et al (2017) identified the microbial diversity of caecal samples from geese using high-throughput sequencing and reported that the phylum Bacteroidetes, Firmicutes, Proteobacteria, Synergistete, Spirochaetes and Actinobacteria were identified as the dominant bacteria in the caecal microbiome of geese.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that Bacteroidetes, Firmicutes and Proteobacteria are numerically dominant phyla in the gut microbiome of animals (Thomas et al 2011), including humans (Qin et al 2010), wild-captured green turtles (Chelonia mydas) (Ahasan et al 2017), loggerhead turtles (Caretta caretta) (Abdelrhman et al 2016), doves, waterfowls and geese (Hird et al 2015;Li et al 2017) and other vertebrates (Ley et al 2008). In the present study, although Proteobacteria made up a large proportion of the sequences in the intestinal microbiome of 0-day turtles, overall, the Firmicutes and Bacteroidetes were the most ubiquitous and common, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial community in the gastrointestinal tract has a major role to play in several physiology processes of the host, such as maintaining intestinal microecological balance, promoting host health, and providing nutrients (Chung et al 2012;Kahrstrom et al 2016;Mohd Shaufi et al 2015;Yamashiro 2017). In addition, the gut microbiome is also associated with gut disease, feed conversion, parasite colonization, and immune system activity of the host (Li et al 2017;Singh et al 2012). Gut microbes can prevent the overgrowth of gut pathogens by building a natural barrier, called 'colonization resistance' that can inhibit the growth of pathogenic bacteria by occupying the same ecological niche (Buffie & Pamer 2013;Ducarmon et al 2019;Scott et al 2015).…”
Section: Introductionmentioning
confidence: 99%